A Mere Machine: The Supreme Court, Congress, and American Democracy - Anna Harvey (Yale University Press, 2013)
On June 28, 2012, the Supreme Court ruled for the fi rst time in seventyfi ve years that Congress had exceeded the limits of its powers under the Spending Clause, the clause of Article I, Section 8, empowering the Congress â€œto pay the Debts and provide for the common Defence and general Welfare of the United States.â€1 Striking a key component of the Patient Protection and Affordable Care Act, signed by President Barack Obama in March of 2010, the Court ruled that Congress could not withhold all federal Medicaid funds from states choosing not to participate in the substantial expansion of Medicaid envisioned by the Act. Instead, states choosing not to participate in the programâ€™s expansion would simply lose the additional federal monies available under the Act to partially fund that expansion. In effect, the Court made the statesâ€™ participation in the Affordable Care Actâ€™s Medicaid expansion, an expansion that had been predicted to extend health insurance to approximately 22.3 million previously uninsured low-income individuals, a purely voluntary choice.2 The Courtâ€™s Spending Clause ruling initially attracted little attention from observers focused on its ruling, in the same case, that Congress could levy a penalty on certain categories of individuals choosing not to purchase private health insurance. But the signifi cance of the Courtâ€™s Medicaid ruling soon became apparent. Within days of the ruling the Republican governors of some of the states with the largest populations of potential recipients under the proposed Medicaid expansion had announced that they would resist any efforts to participate in that expansion, a resistance that would have been virtually unthinkable prior to the Courtâ€™s ruling.3 Other governors announced that they might consider participating in Medicaidâ€™s expansion, but only under broad waivers from program requirements that would allow them to limit recipientsâ€™ eligibility and benefi ts; the Courtâ€™s ruling had given these governors the leverage to demand such waivers.4 The emboldened opposition to Medicaidâ€™s expansion in these states began to put pressure on neighboring states, which would likely face an infl ux of potential Medicaid recipients should they expand eligibility and benefi ts while their neighbors did not